Quality evaluation of ozone-processed Kinnow (Citrus reticulata Blanco) juice at ambient temperature - Aqsa Iqbal; Muhammad Nadeem; Ammara Ainee; Tahir Mahmood Qureshi; Waseem Khalid; Faiqa Malik; Salim-Ur Rehman; Abdul Rehman; Muhammad Zubair Khalid; Naushad Ahmad; Asad Nawaz; Isam A. Mohamed Ahmed (International Journal of Food Properties)
Non-thermal processing has been developed to increase the quality and storage life of fruit juices in response to consumer desire. Ozonation is a recently developed method that generates volatile oxygen atoms that can eliminate a broad spectrum of microbes and extend the shelf stability of food products. The present research was intended to investigate the ozone processing on the physicochemical characteristics, microbiological quality, sensory attributes, and antioxidant potential of Kinnow juice. In this study, Kinnow juice was processed to 150 mg/h of ozone gas at a constant concentration for 5, 10, and 15 min. The sample was then taken in a plastic container and stored at 35°C ± 2 for three months. The results revealed that ozone processing had a significant (p˂0.05) effect on the total phenolics (TP) contents, total flavonoids (TF) contents, total soluble solids (TSS), acidity, total antioxidant activity (TAA) and DDPH radical scavenging activity of Kinnow juice. In addition, the ozonation application also significantly (p˂0.05) decreased the population of the microbes when the ozone time was increased from 5–15 min. Among the treatments, it was observed that T3 had the highest TSS, acidity, TF contents, TAA, and DDPH radical scavenging activity values and the lowest mold and plate counts. Regarding sensory qualities, T0+ showed the highest sensory score during storage. Thus, it may be concluded from the findings of our study that ozone application improved the quality of Kinnow juice by increasing TSS, phytochemicals and decreasing the microbial population, thereby prolonging their shelf life.